Hubungan Morfologi Otot Peroneus dan Stabilitas Fungsional dengan Fungsi Ankle dan Kejadian Ankle Sprain pada Olahragawan - Githa Sugiarta Indraswari; I Putu Gde Surya Adhitya; Indah Pramita; I Putu Yudi Pramana Putra (KOLONI, 2026)
Ankle injuries, particularly ankle sprains, are among the most common injuries in athletes due to high physical activity and biomechanical stress on the ankle joint. Functional stability plays a crucial role in maintaining movement control and balance, and is therefore considered a key factor influencing ankle function and injury risk. This study aimed to determine the relationship between functional stability, ankle function, and the incidence of ankle sprain in athletes. A cross-sectional study was conducted involving 75 athletes aged 15–22 years selected through purposive sampling. Functional stability was assessed using the Y-Balance Test (YBT), ankle function using the Foot and Ankle Outcome Score (FAOS), and ankle sprain incidence through an injury history questionnaire. Data were analyzed using Spearman’s rho test and logistic regression. Significant correlations were found between functional stability and ankle function, particularly in pain and symptom domains (p < 0.05). Additionally, a significant negative correlation was observed between functional stability and ankle sprain incidence (p < 0.05), indicating that better functional stability is associated with a lower risk of injury. Functional stability plays an important role in improving ankle function and reducing the risk of ankle sprain in athletes.Balance training and neuromuscular control exercises are recommended, along with routine screening using the Y-Balance Test for injury prevention.